Shifting FDIs scenario: a case of an African safari. (1st January 2012) - Vadra, Ratna
Foreign direct investment (FDI) is one of the major concepts behind globalisation and a project involving this is of prime relevance to the subject of international business. Moreover, the FDI flows have been from developed to developed countries until recently, when it has started flowing from developed to developing countries as well. In the light of this, a study of the FDI flows in the under-developed to developing nations of the African continent would provide critical knowledge in view of the global economy. Our study aims at observing and analysing the trends of FDI flows in African countries with respect to the various factors that influence it and its importance with respect to the global economy. This paper investigates the new phenomenon of increased FDI in African regions in particular and also discusses the flow of FDI from India to the continent of Africa.